Pembentukan Karakter Religius Santri Melalui Pembiasaan Istighfar Bersama di Pondok Pesantren Hidayatul Mubtadiin Lampung Selatan - Leli Susanti; Nurwinda Apriyani; Mustafida Mustafida (Journal on Education, 2024)
The main objectives of this research are: 1) To determine the formation of the religious character of santri through the habit of istighfar together at the Hidayatul Mubtadiin Sidoharjo Islamic Boarding School, Jati Agung, South Lampung. 2) To determine the supporting and inhibiting factors in istighfar activities with students at the Hidayatul Mubtadiin Sidoharjo Islamic Boarding School, Jati Agung, South Lampung. This research method uses a qualitative approach. The method used in this research is observation, interviews, documentation. The results of the research carried out by researchers regarding the formation of the religious character of students through the habit of istighfar together at the Hidayatul Mubtadiin Islamic Boarding School is to equip the students not only in their religion, but at the Islamic Boarding School there is also non-formal education which makes the Hidayatul Mubtadiin Islamic Boarding School attractive. Supporting factors in forming the religious character of students through the habit of istighfar together are full support from the management, friends/other students, fairly good adjustment/intelligence. The inhibiting factor is the lack of self-awareness of the students, which results in them feeling lazy and unenthusiastic, unable to control their sleepiness and the lack of administrators controlling the students during joint Istighfar habituation activities.